Design of MSE Wall with geotextile reinforcement for temporary mitigation of landslide in Padang Panjang – Sicincin road section (STA 64+100) - Saddam Muhammad; Azwin; Anggraini Vivi; Yuliet Rina (E3S Web of Conferences)
The Padang Panjang - Sicincin roads section was cut off due to a flash flood on Saturday, 11 May 2024. This caused a landslide in the area resulting in the national road access being cut off, and traffic flow was forced to be diverted to several alternative routes. The study aims to obtain the total length of geotextile at any depth (L), the vertical spacing of the layers (Sv), and the lap length (l1) in MSE wall heights at STA 64 + 100. The computation method for external and internal stability (pull out and break), uses the Load Resistance Factor Design (LRFD). From the calculation results for the effective height (He) of the MSE wall of 8 m, the reinforcement length is 6 m, the embedment depth is 0.6 m, the vertical spacing (Sv) is 0.8 m from the internal stability, and the fold length (l1) is 1 m. The design results obtained MSE wall dimensions that are safe for external and internal stability. These dimensions can be used for temporary landslide handling but not long-term. For long-term stability, adding facing elements like secant piles, cantilever walls, and other forms is recommended to avoid erosion due to river water flow.